Dampak Iklan dan Cashback Terhadap Keputusan Pembelian pada E-Commerce Shopee di Kota Surabaya - Kornelia Sarce; Rina Dewi; Bambang karnain; Harsono Teguh; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This study aims to evaluate the effect of advertising and cashback on purchasing decisions on the Shopee e-commerce platform. This study uses a quantitative method involving 100 respondents who are active Shopee users. Data was obtained through questionnaires distributed online. Data analysis was carried out using descriptive analysis, multiple linear regression, data instrument test, classical assumption test, hypothesis testing and determination coefficient test to measure the extent to which advertising and cashback influence purchasing decisions. The results showed that both advertising (X1) and cashback (X2) had a significant effect on purchasing decisions on Shopee e-commerce in Surabaya city. Multiple linear analysis shows that the variables of advertising (X1) and cashback (X2) partially and significantly affect purchasing decisions in e-commerce shopee in the city of Surabaya. Both advertising variables (X1) and cashback (X2) simultaneously have a significant and significant effect on purchasing decisions on e-commerce shopee in the city of Surabaya. The cashback variable which has a more dominant effect on purchasing decisions compared to advertising (X1) can be seen in the highest beta coefficient. These findings indicate that effective marketing strategies, such as attractive advertisements and cashback offers, can increase interest and purchasing decisions. Therefore, Shopee is advised to continue optimizing advertisements and cashback programs to maintain and increase customer loyalty.